Peran Guru dalam Meningkatkan Keterampilan Minat Bakat Siswa melalui Kegiatan Ekstrakurikuler di SD Istiqamah Bandung - Kinesti, Rakanita Dyah Ayu; Maharani, Tiara; Maesaroh, Elisa; Suroyya, Khayya Sa`adatun Nuris; Azkiya, Zafira Zia; Ningsih, Heni Anggraeni (Lembaga Yasin AlSys, 2022)
SD Istiqamah Bandung is an excellent elementary school located in the city of Bandung, West Java. This elementary school is famous for their superior products, namely one of the extracurricular programs held at SD Istiqamah Bandung. This study aims to determine how extracurricular activities are organized at SD Istiqamah Bandung, and how the teacher's role is in developing talents and interests in children through extracurricular activities. This study uses the teacher's role in guiding students' interests and talents. This study uses a qualitative descriptive approach, namely observing directly through observations, written notes while in the field, and documentation. Observations were made with the main focus, namely the role of teachers in extracurricular activities and also how the extracurricular activities themselves at SD Istiqamah Bandung. The participants involved are students who have achievements in several extracurricular activities, teachers and school staff. Extracurricular activities at SD Itiqamah Bandung include 2 types of extracurricular activities, namely general activities and religious activities. General extracurricular activities include: cinematography, archery, scouts, english club, ICT, karate, robotics, choir, and dance. While the religious activities are: tahfidz, qiroat, calligraphy, and small preachers. The teacher's role in extracurricular activities include: Giving affection (attention), Cooperation with parents, Provide training, Improve and motivate, Support extracurricular activities, Conduct assessments. Each major in extracurricular at SD Istiqamah Bandung has its own coaching, so that students can learn their interests and talents with more focus.